(untitled) (Annals of Medical Research, 2022)
Aim: In this study, we examined the factors affecting the psychological symptoms and quality of life of the caregiver parents of the cerebral palsy patients. Materials and Methods: This cross-sectional study was conducted between May-September 2013 in fifty CP patients and their caregivers. Demographic information, parents’ education, family type, households, patients’ siblings, drug usage, rehabilitation hospitalizations (NoRH), and gross motor function levels were recorded. The caregivers completed the psychometric symptom checklist (SCL-90-R) and the QoL questionary (SF-36). Factors affecting SCL-90-R and SF-36 were evaluated by correlation and regression analysis. Results: The proportion of symptomatic parents in the psychiatric evaluation ranged from 26% to 58% in subheadings. Psychological symptoms were mostly correlated with low QoL. Quality of life was lower than the population average in all subheadings. GHI and paranoid thoughts were positively correlated with NoRH. Households’ number was negatively correlated with NoRH (p=0.045, p=0.032, p=0.025). Interpersonal sensitivity and the siblings’ number were positively correlated (p=0.005). Father’s primary school graduation was a risk factor for increased anxiety (OR=0.446, p=0.030). The female CP was a risk for paranoid thoughts (OR=0.410, p=0.025). For SF-36, median scores were low in all components. The nuclear family was a risk factor for low physical components score (OR=-8.123, p=0.009). Not using any medications was a risk factor for a lower mental component score (OR=7.953, p=0.008). Conclusion: The caregiver parents had low QoL and more psychological symptoms. Public healthcare policymakers should plan projects to improve the psychological health and QOL of caregivers.